2017
DOI: 10.3389/fimmu.2017.00618
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Interactions in Schizophrenia: Focus on Vagus Nerve Stimulation and Activation of the Alpha-7 Nicotinic Acetylcholine Receptor

Abstract: Schizophrenia is one of the most debilitating mental disorders and is aggravated by the lack of efficacious treatment. Although its etiology is unclear, epidemiological studies indicate that infection and inflammation during development induces behavioral, morphological, neurochemical, and cognitive impairments, increasing the risk of developing schizophrenia. The inflammatory hypothesis of schizophrenia is also supported by clinical studies demonstrating systemic inflammation and microglia activation in schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 169 publications
(187 reference statements)
0
32
0
2
Order By: Relevance
“…Neurons also have cytokine receptors, suggesting an active bidirectional crosstalk between the immune and nervous systems (Wyss-Coray and Mucke, 2002). Additionally, cytokines have different functions in the central nervous system and can induce neurotoxicity, which appears to contribute to the physiopathology of psychiatric [depression, schizophrenia] and neurodegenerative diseases [Parkinson’s and Alzheimer’s diseases] (Allan and Rothwell, 2003; Corsi-Zuelli et al, 2017; Dantzer et al, 2008). Moreover, since inflammation in the central nervous system, particularly in the hypothalamus, has recently been shown to be intricately involved in the development and maintenance of hypertension (Khor and Cai, 2017), we suggest that the selective and central anti-inflammatory potential of ADN stimulation could be an additional mechanism involved in the baroreflex anti-hypertensive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons also have cytokine receptors, suggesting an active bidirectional crosstalk between the immune and nervous systems (Wyss-Coray and Mucke, 2002). Additionally, cytokines have different functions in the central nervous system and can induce neurotoxicity, which appears to contribute to the physiopathology of psychiatric [depression, schizophrenia] and neurodegenerative diseases [Parkinson’s and Alzheimer’s diseases] (Allan and Rothwell, 2003; Corsi-Zuelli et al, 2017; Dantzer et al, 2008). Moreover, since inflammation in the central nervous system, particularly in the hypothalamus, has recently been shown to be intricately involved in the development and maintenance of hypertension (Khor and Cai, 2017), we suggest that the selective and central anti-inflammatory potential of ADN stimulation could be an additional mechanism involved in the baroreflex anti-hypertensive effects.…”
Section: Discussionmentioning
confidence: 99%
“…4b). Experimental, epidemiological, and clinical trials show that nicotine inhibits inflammation in multiple disorders including ulcerative colitis, arthritis, sepsis, schizophrenia, and Alzheimer’s disease[9699]. However, nicotine has many detrimental side effects limiting its clinical use[100, 101].…”
Section: Neuronal Efferent Network Of Neuromodulationmentioning
confidence: 99%
“…The distal end of the splenic nerve releases norepinephrine, which inhibits the release of TNF-α by spleen macrophages through binding to the β2 adrenergic receptor of spleen lymphocytes that release ACh [92]. Recent review studies have also indicated both peripheral and central anti-inflammatory effects in taVNS, exerted via α7 nAChRs [93]. VNS might have an anti-inflammatory effect on central serotonin levels and affect the HPA axis and cortisol levels [94].…”
Section: Tavns and The Inhibition Of Central And Peripheral Inflammatmentioning
confidence: 99%